All-solid-state batteries
The negative electrode design with ion-conductive adhesive and protective layers in all-solid-state batteries addresses metal protrusion issues, enhancing energy density and durability by preventing short circuits and maintaining sealing.
Patent Information
- Application Number
- JP2022008794
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-01-24
- Publication Date
- 2025-11-06
- Estimated Expiration
- 2042-01-24
AI Technical Summary
All-solid-state batteries using deposition-type negative electrodes face issues with metal protrusion from the electrode edges, leading to short-circuiting and reduced cycle durability when increasing positive electrode capacity for higher energy density.
The negative electrode is designed with a protruding end face bonded to a current collector via an ion-conductive adhesive layer, ensuring the adhesive layer's dimensional change is less than the electrode's during charge and discharge, and incorporating ion-conductive or insulating protective layers to prevent metal protrusion and maintain sealing.
This configuration enhances energy density while preventing short circuits and maintaining cycle durability by controlling metal deposition and reducing stress on the solid electrolyte layer.
Smart Images

Figure 0007765295000001 
Figure 0007765295000002 
Figure 0007765295000003
Abstract
Description
[Technical Field]
[0001] The present invention relates to an all-solid-state battery. [Background technology]
[0002] Patent Document 1 discloses an all-solid-state battery having a configuration that prevents short-circuiting between a positive electrode layer and a negative electrode layer. Specifically, the solid electrolyte layer has an insulator on its outer periphery, and the insulator has a frame shape with a hollow center or frame, and at least a portion of the inner periphery of the frame has a void, and at least a portion of the void is filled with a solid electrolyte. The thickness of the center of the solid electrolyte layer is the same as or greater than the thickness of the void filled with the solid electrolyte. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent No. 6090074 Summary of the Invention [Problem to be solved by the invention]
[0004] However, in the case of an all-solid-state battery using a deposition-type negative electrode, the deposited metal may undergo plastic deformation and migrate outward from the end face of the electrode, potentially preventing the deposited metal from contributing to charge and discharge. This problem is particularly pronounced when the capacity of the positive electrode is increased to improve the battery's energy density.
[0005] Therefore, an object of the present invention is to provide an all-solid-state battery that has a high energy density while preventing short-circuiting between the positive electrode layer and the negative electrode layer. [Means for solving the problem]
[0006] According to one aspect of the present invention, there is provided an all-solid-state battery in which a positive electrode and a negative electrode are stacked with a solid electrolyte layer interposed therebetween. In this all-solid-state battery, the negative electrode has a negative electrode current collector foil and a pair of negative electrode protective layers stacked on either side of the negative electrode current collector foil, wherein an end face of the negative electrode protrudes outward from an end face of the solid electrolyte layer, and at least a portion of the negative electrode protective layer facing the solid electrolyte layer is ion conductive, and a region including at least the end face is bonded to the negative electrode current collector foil via an adhesive layer outside the end face of the solid electrolyte layer. Furthermore, the amount of change in the distance in the stacking direction from the surface of the region of the negative electrode protective layer bonded to the negative electrode current collector foil to the contact surface with the solid electrolyte layer during charge and discharge is greater than the amount of change in the dimension of the adhesive layer during charge and discharge during charge and discharge. [Effects of the Invention]
[0007] According to the above aspect, it is possible to provide an all-solid-state battery having a high energy density while preventing a short circuit between the positive electrode layer and the negative electrode layer. [Brief explanation of the drawings]
[0008] [Figure 1] FIG. 1 is a diagram showing a part of a cross section of a known all-solid-state battery in a fully discharged state. [Figure 2] FIG. 2 is a diagram showing a part of a cross section of a known all-solid-state battery in a charged state. [Figure 3] FIG. 3 is a diagram showing a part of a cross section of an all-solid-state battery in a fully discharged state according to an embodiment of the present invention. [Figure 4] FIG. 4 is a diagram showing a part of a cross section of an all-solid-state battery in a charged state according to an embodiment of the present invention. [Figure 5] FIG. 5 is a diagram showing variations in adhesive layers depending on energy density. [Figure 6] FIG. 6 is a diagram showing a part of a cross section of an all-solid-state battery according to a modified example of the first embodiment in a fully discharged state. [Figure 7] FIG. 7 is a diagram showing a part of a cross section of the all-solid-state battery according to the second embodiment in a fully discharged state. [Figure 8]FIG. 8 is a diagram showing a part of a cross section of an all-solid-state battery according to a modified example of the second embodiment in a fully discharged state. [Figure 9] FIG. 9 is a diagram showing a part of a cross section of the all-solid-state battery according to the third embodiment in a fully discharged state. [Figure 10] FIG. 10 is a diagram showing a part of a cross section of an all-solid-state battery according to a first modified example of the third embodiment in a fully discharged state. [Figure 11] FIG. 11 is a diagram showing a part of a cross section of an all-solid-state battery according to a second modified example of the third embodiment in a fully discharged state. [Figure 12] FIG. 12 is a diagram showing a part of a cross section of an all-solid-state battery according to a third modified example of the third embodiment in a fully discharged state. [Figure 13] FIG. 13 is a diagram showing the manufacturing process of an all-solid-state battery. DETAILED DESCRIPTION OF THE INVENTION
[0009] Hereinafter, an embodiment of the present invention will be described with reference to the accompanying drawings.
[0010] First, the problems with all-solid-state batteries that use a deposition-type negative electrode will be explained with reference to Figures 1 and 2. Figures 1 and 2 are partial cross-sectional views of a known all-solid-state battery, with Figure 1 showing a fully discharged state and Figure 2 showing a state in which metal has been deposited on the negative electrode due to charging.
[0011] When charging from the fully discharged state shown in Figure 1, metal precipitates between the negative electrode current collector foil and the solid electrolyte layer. Because a confining pressure is applied to the all-solid-state battery from both sides in the stacking direction, the precipitated metal (hereinafter also referred to as "deposited metal") undergoes plastic deformation and moves in a direction perpendicular to the stacking direction. Furthermore, as the positive electrode capacity increases to improve the energy density, the amount of deposited metal increases, which may cause it to protrude from the edges of the all-solid-state battery, as shown in Figure 2. By making the edges of the solid electrolyte layer protrude outward from the edges of the positive electrode layer and the negative electrode current collector foil as shown in Figure 1, it is possible to prevent short circuits caused by the deposited metal bypassing the solid electrolyte layer at the edges of the all-solid-state battery and reaching the positive electrode layer. However, since the protruding deposited metal does not contribute to charge and discharge, the greater the amount of protruding deposited metal, the lower the cycle durability. In other words, to improve the energy density of all-solid-state batteries, the problem of reduced cycle durability due to the protruding deposited metal must be solved. A configuration for preventing short circuits caused by deposited metal and improving energy density is described below.
[0012] [First embodiment] 3 and 4 are views showing a part of a cross section of the all-solid-state battery 1 according to this embodiment, with Fig. 3 showing a fully discharged state and Fig. 4 showing a state in which metal has been deposited on the negative electrode due to charging. In the following description, the vertical direction in the drawing is referred to as the stacking direction, and the horizontal direction in the drawing is referred to as the width direction.
[0013] The all-solid-state battery 1 is formed by stacking a plurality of unit cells, each of which has a positive electrode 3 and a negative electrode 4 stacked with a solid electrolyte layer 2 interposed therebetween. Note that a confining pressure is applied to the all-solid-state battery 1 from both sides in the stacking direction to maintain good contact between the layers.
[0014] The positive electrode 3 includes a positive electrode current collector foil 5 and a positive electrode layer 6 formed on both sides of the positive electrode current collector foil 5. A known material is used to form the positive electrode current collector foil 5. The same applies to the positive electrode layer 6.
[0015] The negative electrode 4 includes a negative electrode current collector foil 7 and a negative electrode protective layer 8 disposed on both sides of the negative electrode current collector foil 7. The negative electrode current collector foil 7 is formed from a known material.
[0016] The end faces (negative electrode current collector end face 7A and negative electrode protective layer end face 8A) of the negative electrode 4 protrude outward beyond the solid electrolyte layer end face 2A. In this embodiment, "protruding outward" means protruding in a direction away from the solid electrolyte layer end face 2A in the width direction.
[0017] At least a portion of the region of the anode protective layer 8 facing the solid electrolyte layer 2 has ion conductivity, and at least a region including the end face 8A is adhered to the anode current collector foil 7 outside the end face 2A of the solid electrolyte layer via an adhesive layer 9. The adhesive layer 9 is formed of a known adhesive. Note that the entire anode protective layer 8 of this embodiment is formed of an ion-conductive material.
[0018] The anode protective layer 8 contains at least one of a carbon material (e.g., carbon black) and a solid electrolyte (e.g., a sulfide-based solid electrolyte such as LGPS or LPS) as a material for providing ion conductivity. The anode protective layer 8 may be produced by impregnating a porous resin sheet or a porous metal sheet with the carbon material and the solid electrolyte, or by coating a frame of a frame-shaped resin sheet or a metal sheet with a mixture of the carbon material and the solid electrolyte and a binder such as a resin. The thickness of the anode protective layer 8 in this embodiment is 1 to 100 μm (more preferably 1 to 10 μm).
[0019] When charging is performed from the fully discharged state shown in Fig. 3, metal is deposited between the negative electrode current collector foil 7 and the negative electrode protective layer 8 as shown in Fig. 4 (hereinafter, the deposited metal is also referred to as metal deposit 10), and the distance in the stacking direction between the negative electrode current collector foil 7 and the negative electrode protective layer 8 increases in the deposited portion. However, the negative electrode current collector foil 7 and the negative electrode protective layer 8 are bonded near their ends by an adhesive layer 9, and even if the amount of metal deposit 10 increases, it does not protrude outside the solid electrolyte layer end surface 2A as shown in Fig. 2 above. In other words, the adhesive layer 9 blocks the movement of the metal deposit 10 in the width direction.
[0020] As the metal is deposited, the dimension of the adhesive layer 9 in the stacking direction also changes due to the elastic force of the adhesive used. However, the amount of this change (B1 - B0 in the figure) is smaller than the amount of change in the stacking direction distance (A1 - A0 in the figure) from the surface 8B of the region where the negative electrode protective layer 8 is adhered to the negative electrode current collector foil 7 to the contact surface 8C with the solid electrolyte layer 2. That is, the relationship A1 - A0 > B1 - B0 holds.
[0021] The fact that the above relationship holds means that while the amount of the deposited metal 10 is relatively small, only the negative electrode protective layer 8 is deformed and the dimension of the adhesive layer 9 in the stacking direction hardly changes. Thereafter, the dimension of the adhesive layer 9 in the stacking direction also increases due to being pulled in the stacking direction by the deformed negative electrode protective layer 8.
[0022] On the other hand, when A1 - A0 < B1 - B0, the negative electrode protective layer 8 will push up the adhesive layer 9 when the amount of the deposited metal 10 is relatively small. That is, an input in the peeling direction will occur in the adhesive layer 9 every time charging is performed, so the sealing property of the adhesive layer 9 is likely to decrease, and there is a possibility that the function of blocking the movement of the deposited metal 10 in the width direction will be impaired.
[0023] In order to further improve the energy density, it is desirable that the deformable region of the negative electrode protective layer 8 be wider. Therefore, the dimension of the adhesive layer 9 in the width direction is desirably as narrow as possible (for example, 10 mm or less, more preferably 3 mm or less) within a range where an adhesive force capable of maintaining the dimensional change with the relationship A1 - A0 > B1 - B0 can be ensured.
[0024] Also, the distance C0 between the end face 2A of the solid electrolyte layer and the adhesive layer 9 is desirably at least equal to or greater than the dimension of the deposited metal 10 in the stacking direction at full charge in order to ensure a deformable region of the negative electrode protective layer 8 corresponding to the amount of the deposited metal 10. By ensuring such a deformable region of the negative electrode protective layer 8, it is possible to suppress the application of stress to the solid electrolyte layer 2 and the application of shear force to the negative electrode protective layer 8 during charge and discharge.
[0025] 5 is a diagram showing variations of the adhesive layer 9 for dealing with a larger positive electrode capacity. Note that although the reference numerals of the various parts are omitted, they are the same as those in FIGS.
[0026] Since the amount of change in the dimension of the deposited metal 10 in the stacking direction increases as the positive electrode capacity increases, the deformable area of the negative electrode protective layer 8 must also be increased to increase the positive electrode capacity. Therefore, the width direction dimension of the adhesive layer 9 is set according to the required size of the deformable area of the negative electrode protective layer 8 (FIG. 5(A)).
[0027] In the case of Fig. 5B, where the change in the dimension of the deposited metal 10 in the stacking direction is larger than in Fig. 5A, the deformable region of the anode protective layer 8 needs to be larger than in the case of Fig. 5A. Therefore, the width direction dimension of the adhesive layer 9 is made smaller than in the case of Fig. 5A, thereby ensuring the deformable region of the anode protective layer 8.
[0028] In order to ensure a deformable region of the negative electrode protective layer 8, the dimension of the adhesive layer 9 in the stacking direction may be increased as in the case of Fig. 5(C). Note that in the left diagram of Fig. 5(C), the side surface of the adhesive layer 9 is not bonded to the negative electrode protective layer 8.
[0029] By ensuring a deformable region of the anode protective layer 8 using the above-mentioned method, the positive electrode capacity can be increased, and as a result, the energy density can be increased. Note that (A) to (C) in Fig. 5 show examples of variations of the adhesive layer 9 for accommodating a larger positive electrode capacity, and the configuration for ensuring a deformable region of the anode protective layer 8 is not limited to these.
[0030] 6 is a diagram showing a part of a cross section of the all-solid-state battery 1 according to a modified example of this embodiment in a fully discharged state. This modified example also falls within the scope of the present invention, just like the above-described embodiment.
[0031] The difference between the above embodiment and this modification is that the anode protective layer 8 of this modification includes an insulating portion 11 that is insulated on the surface of the solid electrolyte layer 2 side in a region that protrudes outward from the end face 6A of the cathode layer 6. The insulating portion 11 is made of, for example, a resin, a metal oxide, or a mixture thereof.
[0032] By providing the insulating portion 11 in this manner, even when the amount of change in the dimension of the negative electrode 4 in the stacking direction due to charge and discharge is large, as shown in (C) of Figure 5, it is possible to prevent a short circuit between the negative electrode protective layer 8 and the positive electrode layer 6 and the positive electrode current collecting foil 5.
[0033] As described above, in this embodiment, in the all-solid-state battery 1 in which the positive electrode 3 and the negative electrode 4 are stacked with the solid electrolyte layer 2 interposed therebetween, the negative electrode 4 includes the negative electrode current collector foil 7 and a pair of negative electrode protective layers 8 stacked on either side of the negative electrode current collector foil 7, and the end face of the negative electrode 4 protrudes outward beyond the end face 2A of the solid electrolyte layer 2. At least a portion of the region of the negative electrode protective layer 8 facing the solid electrolyte layer 2 is ion conductive, and a region including at least the end face is bonded to the negative electrode current collector foil 7 via the adhesive layer 9 outside the end face of the solid electrolyte layer 2. By bonding the vicinity of the end in this manner, deformation of the deposited metal 10, for example, as shown in FIG. 2, can be suppressed. Furthermore, because the end of the negative electrode 4 is located outside the end of the solid electrolyte layer 2, a decrease in charge / discharge capacity and shear stress on the solid electrolyte layer 2 during discharge can be prevented.
[0034] Furthermore, the change (A1-A0) in the distance in the stacking direction from the surface of the region of the negative electrode protective layer 8 bonded to the negative electrode current collector foil 7 to the contact surface with the solid electrolyte layer 2 during charging and discharging is greater than the change (B1-B0) in the dimension of the adhesive layer 9 during charging and discharging. This makes it easier to maintain the sealing function by preventing breakage or peeling of the adhesive portion, and ultimately makes it possible to improve the energy density of the all-solid-state battery 1.
[0035] In this embodiment, the anode protective layer 8 includes an insulating portion 11 that has been insulated on the surface of the region of the anode protective layer 8 that protrudes outward from the end face 3A of the positive electrode 3, facing the solid electrolyte layer 2. This improves the electronic insulation of the region of the anode protective layer 8 that protrudes outward from the end face 3A of the positive electrode 3, and prevents a short circuit between the anode protective layer 8 and the positive electrode layer 6 or the positive electrode current collector foil 5 due to deformation of the deposited metal 10, even if the thickness of the anode 4 changes significantly during charge and discharge.
[0036] In this embodiment, the anode protective layer 8 contains at least one of a carbon material and a solid electrolyte as an ion-conductive material, thereby ensuring ion conductivity and preventing metal deposited between the anode protective layer 8 and the anode current collector foil 7 from penetrating and reaching the solid electrolyte layer 2.
[0037] In this embodiment, the negative electrode protective layer 8 contains a solid electrolyte as an ion-conductive material, which can suppress an increase in the internal resistance of the all-solid-state battery 1.
[0038] [Second embodiment] 7 is a diagram showing a portion of a cross section of the all-solid-state battery 1 according to this embodiment in a fully discharged state. The difference from FIG. 3 is the anode protective layer 8. The anode protective layer 8 of this embodiment is composed of an ion-conductive material-free region 13 extending from the end face 8A to the inside of the solid electrolyte layer end face 2A, and an ion-conductive material-containing region 12 located further inside.
[0039] The ion-conductive material-free region 13 is made of a resin sheet that has electronic insulation and a higher air permeability than the ion-conductive material-containing region 12. Examples of suitable materials include polypropylene, polyethylene terephthalate, polyethylene naphthalate, and polyacrylonitrile. The use of a resin sheet ensures flexibility in the region that deforms during charging and discharging. In other words, the strength against repeated deformation during charging and discharging can be increased. Furthermore, the relatively high air permeability of the region used for adhesion further enhances the sealing ability against the deposited metal 10.
[0040] As described above, the air permeability of the ion-conductive material-free region 13 may be greater than that of the ion-conductive material-containing region 12, but it is preferable that the measurement result using the Gurley tester method standardized by JIS is 1000 seconds / 100 ml or more, and more preferably 5000 seconds / 100 ml or more.
[0041] By providing the ion-conductive material-free region 13, it is possible to prevent short circuits between the negative electrode protective layer 8 and the positive electrode layer 6 and the positive electrode current collector foil 5, as in the above-described modified example, and furthermore, strength is improved.
[0042] The smaller the ion-conductive material-containing region 12, the smaller the region of the anode protective layer 8 that is available for the battery reaction. Therefore, the width direction dimension D of the portion of the ion-conductive material-free region 13 that is located inside the solid electrolyte layer end face 2A is preferably such that the region available for the battery reaction does not become excessively narrow. The specific value varies depending on the size of the all-solid-state battery 1, but for sizes generally expected for vehicle batteries, it is preferably within 2 mm, and more preferably within 1 mm.
[0043] 8 is a diagram showing a part of a cross section of the all-solid-state battery 1 according to a modified example of this embodiment in a fully discharged state. This modified example also falls within the scope of the present invention, just like the above-described embodiment.
[0044] The difference from FIG. 7 is that at least a portion of the ion-conductive material-free region 13, in this case the portion inside the end surface 2A of the solid electrolyte layer, is adhered to the solid electrolyte layer 2 via an adhesive layer 14.
[0045] As a result, even if metal precipitates between the solid electrolyte layer 2 and the anode protective layer 8, the adhesive layer 14 acts as a seal, preventing the precipitated metal 10 from spilling out beyond the solid electrolyte layer end surface 2A.
[0046] As described above, in this embodiment, the anode protective layer 8 is composed of the ion-conductive material-free region 13 extending from the end face to the inside of the end face 2A of the solid electrolyte layer, and the ion-conductive material-containing region 12 located inside the ion-conductive material-free region 13. This improves the electronic insulation and strength of the region of the anode protective layer 8 that protrudes outward from the end face 3A of the positive electrode 3, and prevents a short circuit between the anode protective layer 8 and the positive electrode layer 6 or the positive electrode current collector foil 5 due to deformation of the deposited metal 10, even if the thickness of the anode 4 changes significantly during charge and discharge.
[0047] In this embodiment, at least a portion of the ion-conductive material-free region 13 of the anode protective layer 8 is adhered to the solid electrolyte layer 2 via the adhesive layer 14. This improves the sealing performance against metal deposited between the anode protective layer 8 and the solid electrolyte layer 2.
[0048] In this embodiment, the ion-conductive material-free region 13 of the negative electrode protective layer 8 is made of a resin sheet that has electronic insulation properties and higher air permeability than the ion-conductive material-containing region 12. This allows the ion-conductive material-free region 13 to maintain its flexibility while improving its sealing performance.
[0049] [Third embodiment] 9 is a diagram showing a part of a cross section of the all-solid-state battery 1 according to this embodiment in a fully discharged state. The difference from FIG. 3 is that the end face 3A of the positive electrode 3 is located more inward in the width direction than the end 2A of the contact portion between the negative electrode protective layer 8 and the solid electrolyte layer 2.
[0050] With the above configuration, when the anode protective layer 8 is deformed due to a change in the thickness of the anode 4, a short circuit caused by contact between the anode protective layer 8 and the positive electrode 3 bypassing the solid electrolyte layer 2 is less likely to occur.
[0051] 10 is a diagram showing a part of a cross section of the all-solid-state battery 1 according to a first modified example of this embodiment in a fully discharged state. This modified example also falls within the scope of the present invention, just like the above-described embodiment.
[0052] 9 in that the end face 5A of the positive current collector foil 5 is located at approximately the same position in the width direction as the end face 2A of the solid electrolyte layer, and that a support portion 15 is provided in the gap between the positive current collector foil 5 and the solid electrolyte layer 2 outside the end face 6A of the positive electrode layer 6. The support portion 15 is formed by applying and drying a resin, an insulating slurry, or the like.
[0053] 9 , in the case where the end face 3A of the positive electrode 3 is located inside the end 2A of the contact portion between the anode protective layer 8 and the solid electrolyte layer 2 and the outside of the end face 3A of the positive electrode 3 is hollow, when the thickness of the anode 4 increases due to metal deposition, bending stress is generated in the solid electrolyte layer 2 with the end of the positive electrode layer 6 as a fulcrum. Therefore, when charge and discharge are repeated, the solid electrolyte layer 2 is repeatedly bent, and in the case of an all-solid-state battery 1 with a large amount of deposited metal 10, cracks may occur in the solid electrolyte layer 2.
[0054] In this regard, if the configuration includes the support portion 15 as in this modified example, bending deformation of the solid electrolyte layer 2 can be suppressed, and therefore the occurrence of cracks can be suppressed.
[0055] 11 is a diagram showing a part of a cross section of the all-solid-state battery 1 according to a second modified example of this embodiment in a fully discharged state. This modified example also falls within the scope of the present invention, just like the above-described embodiment.
[0056] 10 is that the support portion 15 is formed as part of the solid electrolyte layer 2. The configuration of this modification also provides the same effects as the first modification.
[0057] 12 is a diagram showing a part of a cross section of the all-solid-state battery 1 according to a third modified example of this embodiment in a fully discharged state. This modified example also falls within the scope of the present invention, just like the above-described embodiment.
[0058] 10 is that the distance E2 from the end of the contact portion between the anode protective layer 8 and the solid electrolyte layer 2 to the end face of the cathode layer 6 is smaller than the distance E1 in Fig. 10, that is, the cathode layer 6 is wider in the width direction, and accordingly the support portion 15 protrudes outward in the width direction. The configuration of this modification example has the same effects as the first modification example, and also has the effect of being able to increase the area of the cathode layer 6 (that is, to increase the cathode capacity).
[0059] As described above, in this embodiment, the end face 3A of the positive electrode 3 is located inside the end 2A of the contact portion between the negative electrode protective layer 8 and the solid electrolyte layer 2. This further reduces the occurrence of a short circuit between the negative electrode protective layer 8 and the positive electrode 3.
[0060] In this embodiment, the support portion 15 is formed as part of the solid electrolyte layer 2 or as a separate member from the solid electrolyte layer 2, and is disposed outside the end face 3A of the positive electrode 3. This can suppress the occurrence of cracks in the solid electrolyte layer 2 due to changes in the thickness of the negative electrode 4 during charge and discharge.
[0061] [Manufacturing method] Next, a method for manufacturing the all-solid-state battery 1 will be described with reference to FIG.
[0062] Here, a description will be given of a manufacturing method of the all-solid-state battery 1 shown in Fig. 3 and explained in the first embodiment. All-solid-state batteries 1 according to other embodiments and the like are also manufactured by basically the same method, although there are differences such as the provision of an insulating section 11 (Fig. 6), the provision of an ion-conductive material-free region 13 (Fig. 7), the provision of an adhesive layer 14 (Fig. 8), a different width dimension of the positive electrode 3 (Fig. 9), and the provision of a support section 15.
[0063] The all-solid-state battery 1 is formed by stacking unit cells, each having a positive electrode 3 formed on one surface of a solid electrolyte layer 2 and a negative electrode 4 formed on the other surface. However, during production, a positive electrode-solid electrolyte assembly 16, which is an assembly of the positive electrode 3 and the solid electrolyte layer 2, and a negative electrode assembly 17, which is an assembly of the negative electrode current collector foil 7 and the negative electrode protective layer 8, are separately produced, and then the two assemblies are stacked together.
[0064] First, the steps for producing the positive electrode-solid electrolyte assembly 16 will be described with reference to steps (A1) to (A3) in FIG.
[0065] In step (A1), a positive electrode layer 6 is formed by coating or the like on both sides of a positive electrode current collector foil 5. In the subsequent step (A2), a solid electrolyte layer 2 is formed by coating, transfer, or the like on the positive electrode layer 6 formed in step (A1). This produces a positive electrode-solid electrolyte assembly 16 shown in step (A3).
[0066] Next, the steps of producing the negative electrode assembly 17 will be described with reference to steps (B1) to (B3) in FIG.
[0067] In step (B1), adhesive layers 9 are formed by coating or the like near the edges of both sides of the negative electrode current collector foil 7. In the subsequent step (B2), negative electrode protective layers 8 formed by coating or the like are provided on both sides of the negative electrode current collector foil 7. At this time, the edges of the negative electrode protective layers 8 are bonded to the negative electrode current collector foil 7 via the adhesive layers 9. This produces a negative electrode assembly 17 shown in step (B3).
[0068] Then, in step (C), the positive electrode-solid electrolyte assembly 16 and the negative electrode assembly 17 are laminated together by a method such as press lamination.
[0069] There are various options for the solvent to be used during coating depending on the material to be coated and the material to be coated, etc. However, when a production method is used in which a positive electrode 3 is formed on one surface of a solid electrolyte layer 2 and a negative electrode 4 is formed on the other surface in a series of steps, the solvents that can be used in each coating step are limited to those that do not interfere with other coating steps.
[0070] In contrast, in the present invention, the cathode-solid electrolyte assembly 16 and the anode assembly 17 are separately fabricated and then laminated by a method such as press lamination, so that a solvent suitable for fabricating the cathode-solid electrolyte assembly 16 and a solvent suitable for the anode assembly 17 can be selected separately. In other words, the number of solvent options increases.
[0071] It goes without saying that the present invention is not limited to the above-described embodiment, and various modifications can be made within the scope of the technical concept described in the claims. [Explanation of symbols]
[0072] 1 All-solid battery, 2 Solid electrolyte layer, 3 Positive electrode, 4 Negative electrode, 5 Positive electrode current collector foil, 6 Positive electrode layer, 7 Negative electrode current collector foil, 8 Negative electrode protective layer, 9 Adhesive part, 10 Deposited metal, 15 Support part
Claims
1. In an all-solid-state battery in which a positive electrode and a negative electrode are stacked with a solid electrolyte layer interposed therebetween, the negative electrode includes a negative electrode current collector foil and a pair of negative electrode protective layers laminated with the negative electrode current collector foil sandwiched therebetween, an end face of the negative electrode protrudes outward beyond an end face of the solid electrolyte layer; at least a part of a region of the anode protective layer facing the solid electrolyte layer has ion conductivity, and a region including at least an end face of the anode protective layer is bonded to the anode current collector foil via an adhesive layer outside the end face of the solid electrolyte layer; a change in a distance in a stacking direction from a surface of a region of the negative electrode protective layer that is bonded to the negative electrode current collecting foil to a contact surface with the solid electrolyte layer, which change with charge and discharge, is larger than a change in a dimension of the adhesive layer in the stacking direction, which change with charge and discharge.
2. The all-solid-state battery according to claim 1, the anode protective layer has an insulating portion that is insulated on a surface of the anode protective layer facing the solid electrolyte layer in a region that protrudes outward from the end face of the positive electrode.
3. The all-solid-state battery according to claim 1 or 2, the anode protective layer comprises an ion-conductive material-free region extending from an end surface to an inner portion of the end surface of the solid electrolyte layer, and an ion-conductive material-containing region extending inward from the ion-conductive material-free region.
4. The all-solid-state battery according to claim 3, the negative electrode protective layer is such that at least a portion of the ion-conductive material-free region is adhered to the solid electrolyte layer via the adhesive layer.
5. The all-solid-state battery according to any one of claims 1 to 4, an end face of the positive electrode is located inside an end of a contact portion between the negative electrode protection layer and the solid electrolyte layer.
6. The all-solid-state battery according to claim 5, a support portion formed of a part of the solid electrolyte layer or a separate material from the solid electrolyte layer, and disposed outside an end face of the positive electrode.
7. The all-solid-state battery according to any one of claims 1 to 6, the anode protective layer contains a carbon material as the ion-conductive material.
8. The all-solid-state battery according to any one of claims 1 to 7, the anode protective layer contains a solid electrolyte as the ion-conductive material.
9. The all-solid-state battery according to any one of claims 1 to 8, the region without ion conductivity of the anode protective layer is formed of a resin sheet that has electronic insulation and a higher air permeability than the region with ion conductivity.
Citation Information
Patent Citations
Coating method of ultraviolet curable paint at site
JP1985090074A
All-solid battery
JP2020136018A
All-solid battery
JP2021034199A
Solid battery
JP2021197302A